Construction of Media Reality: Analysis The Journalists Affecting Factors in Reporting Environmental Climate Change Issue - Ridzki Rinanto Sigit; Rubiyanto Rubiyanto; Akita Arum Verselita (Scriptura, 2025)
Climate change is one of the most pressing global issues, yet its complexity often presents challenges for journalists in constructing accurate and compelling narratives. This study uses Berger and Luckmann's theory of the social construction of reality to understand how journalists shape climate change narratives in their journalistic practice. As an initial step, researchers distributed questionnaires to 30 environmental journalists, followed by in-depth interviews with five key informants. The study identified key determinants such as curiosity, professional experience, and critical reflection, as well as organizational factors including editorial support, access to training, and newsroom dynamics. The findings highlight the transformative role of journalists in shifting from traditional reporting to solutions-oriented journalism, which aims to inspire hope, motivate action, and support societal responses to climate change. The findings reveal that journalists with broader networks and stronger newsroom interactions tend to develop more in-depth narratives, contribute to solutions-based storytelling, and mobilize public awareness. An editorial environment that fosters autonomy and collaboration helps sustain journalistic engagement with environmental issues long-term. This study underscores the importance of micro-level interactions in shaping macro-level social narratives about climate change, highlighting journalists not only as conveyors of information but also as active agents of social transformation.